Ad

Y=2x/3

example: if X=3 the Y=(2*3)/3 = 2; 2*3 - 3*2 = 6 - 6 = 0

But this is no motherborad problem.

Posted on Jan 02, 2011

Ad

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)

click here to download the app (for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

Ad

This is no linear system. You cannot solve it like that using the matrix techniques. Haven't you made a mistake in writing the equations?

If that is tryly the system you want to solve, I suggest that you make a change of variables as follows:

X=1/x , Y= 1/y, Z=1/z (it being understood that x, y, z cannot be equal to 0). You will have to exclude the values x=0, y=0, z=0

Not I am not being sloppy, X and x are different entities, same with Y and y, Z and z.

Your system becomes

**2X+3Y-1Z=26**

1X+3Y-2Z=36

2X+4Y-5Z=52

Now that is a linear system. Solve it using matrices or Cramer's rule, When you obtain X, Y, and Z, get x=1/X, y=1/y, z=1/Z

The actual implementation of the solution method will depend on the exact model of calculator you are using. Not knowing that, I cannot advise you how to do it.

If I have not made any mistakes, the results are X=-58/9,Y=106/9, Z=-32/9. And x, y, z are just the reciprocals of their namesake.

If that is tryly the system you want to solve, I suggest that you make a change of variables as follows:

X=1/x , Y= 1/y, Z=1/z (it being understood that x, y, z cannot be equal to 0). You will have to exclude the values x=0, y=0, z=0

Not I am not being sloppy, X and x are different entities, same with Y and y, Z and z.

Your system becomes

1X+3Y-2Z=36

2X+4Y-5Z=52

Now that is a linear system. Solve it using matrices or Cramer's rule, When you obtain X, Y, and Z, get x=1/X, y=1/y, z=1/Z

The actual implementation of the solution method will depend on the exact model of calculator you are using. Not knowing that, I cannot advise you how to do it.

If I have not made any mistakes, the results are X=-58/9,Y=106/9, Z=-32/9. And x, y, z are just the reciprocals of their namesake.

Dec 13, 2013 | Office Equipment & Supplies

E(2X+3Y) is simply E(2X)+E(3Y) which is 2E(X)+3E(Y) or 2*5+3*8. I'll let you do the final bit of arithmetic yourself.

Mar 06, 2013 | Office Equipment & Supplies

The x intercept is where your line will cross the x axis. Therefore, the value for y at this point is 0. Substitute 0 for y in this equation and solve for x.

6x + 3(0) = 27

x = 27/6

x = 4 1/2

x intercept = (4 1/2, 0)

Follow the same reasoning for the y intercept.

6(0) + 3y = 27

y = 27/3

y = 9

y intercept = (0,9)

Now plot these two points and draw your line through them.

6x + 3(0) = 27

x = 27/6

x = 4 1/2

x intercept = (4 1/2, 0)

Follow the same reasoning for the y intercept.

6(0) + 3y = 27

y = 27/3

y = 9

y intercept = (0,9)

Now plot these two points and draw your line through them.

May 18, 2012 | SoftMath Algebrator - Algebra Homework...

To find the solution, first find the value of y for each equation.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

**y = 2x - 1**

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

**y = -4x + 5**

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

**x=1**

Now substitute x=1 into either original equation:

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

**y = 1**

Therefore the solution is x=1 and y=1

Good luck, I hope that helps.

Joe.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

Good luck, I hope that helps.

Joe.

Nov 09, 2011 | Texas Instruments TI-84 Plus Silver...

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

You can solve it with following method.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

Mar 03, 2010 | Office Equipment & Supplies

I am sorry to be the messenger with bad news, but this calculator does not do symbolic algebra. It does not have a solve function either.

You do have 5 memory variables in which you can store numerical values but it will not do you any good in this particular case.

Anyway, there is nothing you can do with such an expression (IT IS NOT an equation, just an expression) , except some cosmetic change 2x(2x-3y) or expand it 4x^2-6xy.

You do have 5 memory variables in which you can store numerical values but it will not do you any good in this particular case.

Anyway, there is nothing you can do with such an expression (IT IS NOT an equation, just an expression) , except some cosmetic change 2x(2x-3y) or expand it 4x^2-6xy.

Feb 11, 2010 | Texas Instruments TI-34II Explorer Plus...

(13)3/8-(6)15/16

Jun 17, 2008 | Texas Instruments TI-84 Plus Silver...

B. 2((2-Y)/3)-Y=3

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

Nov 22, 2017 | Computers & Internet

59 people viewed this question

Usually answered in minutes!

×